Feasibility and acceptability of time-restricted eating in a group of adults with multiple sclerosis - Wingo, Brooks C.; Rinker, John R.; Green, Kathryn; Peterson, Courtney M. (Frontiers in Neurology, 2023)
Introduction Intermittent fasting (IF) has become a popular dietary pattern for adults with multiple sclerosis (MS), and initial studies in animal models and human trials indicate promising results for improving symptoms and slowing disease progression. Most studies published to date have focused on alternate day fasting or fasting mimicking diets including a 5:2 pattern, in which participants greatly restrict calorie intake on two non-consecutive days and eat regularly on other days; however, time restricted eating (TRE) may be equally effective for improving symptoms and may lead to better long term adherence due to its focus only on the time of day in which calories are consumed with no restriction on number of calories or types of food consumed. Methods The purpose of this pilot study was to determine the feasibility and acceptability of a TRE intervention in adults with relapsing remitting MS (RRMS). Participants (n = 12) were instructed to eat all food within an 8-h window every day and fast the remaining 16 h for 8 weeks. Results The eating pattern was determined to be feasible based on retention rates (n = 11; 92%) and acceptable based on participant feedback. Discussion Exploratory results of changes in cognition, pain, and fatigue, indicate that further study of TRE in this population is warranted. Clinical trial registration https://clinicaltrials.gov/ct2/show/NCT04389970; NCT04389970.